Quality of life and mental health in children with long COVID - Lieke C. E. Noij; Coen R. Lap; Michiel A. J. Luijten; Simone Hashimoto; Lorynn Teela; Kim J. Oostrom; Mattijs W. Alsem; Marlies A. van Houten; Giske Biesbroek; Lotte Haverman; Anke H. Maitland-van der Zee; Johannes B. van Goudoever; et al. (Communications Medicine)
Abstract Background Pediatric Long COVID (PLC) is a heterogeneous condition, which can have a substantial impact on daily life of children and adolescents. This study aimed to evaluate health related quality of life (HRQoL), and mental and social health of children with PLC, in relation to children with other chronic health conditions (CHC) and from the general population (GP) during the pandemic. Methods Dutch children (8-18 years) with PLC (n = 106, 31% male) were included between May 2021 and March 2023. Reference data was available from a CHC-cohort (n = 90, 56% male) and GP-cohort (n = 844, 47% male) during the first wave of the pandemic (April–May, 2020). Participants completed the Pediatric Quality of Life Inventory (PedsQL) 4.0 and Patient-Reported Outcomes Measurement Information System (PROMIS) instruments (Anxiety, Anger, Depressive symptoms, Sleep-Related Impairment (SRI), and Peer Relationships). Mean scores were analyzed using adjusted ANCOVA. Relative risks (RR (95% CI)) were calculated for impaired HRQoL and severe PROMIS scores. Results Children with PLC report high proportions of impaired HRQoL (84%, RR = 3.67 (2.35–5.74)), and have significantly lower PedsQL scores than children with CHC. Children with PLC also exhibit worse PROMIS T-scores of Anxiety, Depressive Symptoms, and SRI than children from the CHC- and GP-cohorts (mean difference range 2.2–9.8 (95%CI 0.6–11.7)), and significantly higher risks of severe anxiety (17%), depressive symptoms (18%), and SRI (17%). Conclusions PLC can severely impact HRQoL and mental and social health in children. Screening of these outcomes and individualized management of children with PLC should be a vital part of clinical care for these highly burdened patients.